Optimizing user loyalty through user interface quality in MSME mobile application: A study on product customization’s mediating role - Sovania, Erina; Armanu, Armanu; Rohman, Fatchur; Mugiono, Mugiono (Edelweiss Applied Science and Technology, 2025)
This study investigates the complex relationships among user interface quality, product customization, and gamification, with the aim of determining their combined impact on user loyalty in mobile marketplace applications targeted at Indonesian MSMEs. Utilizing SmartPLS 4 and structural equation modeling (SEM), the research analyzes data from 400 users of the Umkm Bangkit mobile application in Central Java, based on the Stimulus-Organism-Response (S-O-R) paradigm. The findings highlight the critical role of a high-quality user interface in enhancing user loyalty by encouraging increased user engagement and facilitating effective customization. Interestingly, the anticipated moderating effect of gamification on the relationship between customization and user loyalty was not supported. Platform stakeholders should prioritize improving user interface design and customization tools to foster user loyalty. Despite gamification’s potential, cautious implementation is recommended until more empirical evidence is available. The study’s focus on Central Java limits the generalizability of its findings. Potential sample bias and reliance on self-reported data may also influence the applicability of the results to a broader population. Additionally, the impact of external factors on user loyalty remains unexplored. This research offers new insights into the interaction between user interface quality, product customization, and gamification in mobile marketplace applications, contributing valuable knowledge to the field. It provides practical recommendations for stakeholders seeking to enhance user engagement and loyalty strategies, emphasizing the importance of user interface design and customization while advocating a cautious approach to integrating gamification elements.